Analyzing the need for badminton courses: perspectives of lecturers and students - Silvi Aryanti; Fitri Agung Nanda; Soleh Solahuddin; Samsul Azhar; Anisa Anisa; Maryatul Qibtiyah (Sriwijaya Journal of Sport, 2026)
Research Problems: Learning in badminton courses is still predominantly conducted through conventional methods, resulting in limited student engagement, motivation, and opportunities for interactive learning. In addition, the utilization of digital game-based learning media in badminton instruction remains relatively low, despite the increasing demand for innovative learning approaches that align with students’ characteristics and technological developments. Research Objectives: This study aims to analyze the need for Baamboozle-based learning media in badminton courses from the perspectives of lecturers and students in the Physical Education Study Program. Methods: This study employed a quantitative descriptive research design. The research subjects consisted of lecturers and students of the Physical Education Study Program, Faculty of Teacher Training and Education, Universitas Sriwijaya. Data were collected using a needs analysis questionnaire designed to identify perceptions regarding the necessity, usefulness, attractiveness, and potential implementation of Baamboozle-based learning media in badminton courses. The collected data were analyzed descriptively using percentages and mean scores. Results: The results of the needs analysis revealed that both lecturers and students demonstrated highly positive perceptions toward the implementation of Baamboozle-based learning media. Lecturers reported favourable evaluations regarding its usability, ability to increase learning motivation, and potential as a formative assessment tool. Similarly, students expressed strong interest in game-based learning media that are interactive, practical, engaging, and compatible with their learning preferences. The findings indicate that many respondents agreed that the integration of Baamboozle could enhance participation, collaboration, and learning effectiveness in badminton courses. Conclusion: Based on these findings, the need for the development of Baamboozle-based learning media in badminton courses is considered very high. Baamboozle has the potential to serve as an innovative instructional medium that supports active, collaborative, enjoyable, and technology-enhanced learning experiences. Therefore, the development and implementation of Baamboozle-based learning media are recommended to improve the quality of badminton learning in higher education settings.